Herpesvirus infections, antiviral treatment, and the risk of dementia—a registry‐based cohort study in Sweden. Issue 1 (14th February 2021) - Lopatko Lindman, Karin; Hemmingsson, Eva‐Stina; Weidung, Bodil; Brännström, Jon; Josefsson, Maria; Olsson, Jan; Elgh, Fredrik; Nordström, Peter; Lövheim, Hugo
Abstract: Introduction: Herpesviruses, including Herpes simplex virus type 1 (HSV1) and varicella zoster‐virus (VZV), have been implicated in Alzheimer's disease (AD) development. Likewise, antiviral treatment has been suggested to protect against dementia development in herpes‐infected individuals. Methods: The study enrolled 265, 172 subjects aged ≥ 50 years, with diagnoses of VZV or HSV, or prescribed antiviral drugs between 31 December 2005 and 31 December 2017. Controls were matched in a 1:1 ratio by sex and birth year. Results: Antiviral treatment was associated with decreased risk of dementia (adjusted hazard ratio [HR] 0.89, 95% confidence interval [CI] 0.86 to 0.92), while herpes infection without antiviral drugs increased the risk of dementia (adjusted HR 1.50, 95% CI 1.29 to 1.74). Discussion: Antiviral treatment was associated with a reduced long‐term risk of dementia among individuals with overt signs of herpes infection. This is consistent with earlier findings indicating that herpesviruses are involved in the pathogenesis of AD.